Analisis Kinerja Keuangan Dengan Menggunakan Rasio Keuangan (Studi Kasus Pada Javenir Pusat Souvenir Dan Oleh-Oleh Khas Solo) - MAYASARI, HANIFAH, Dr. Syamsudin, M.M (2017)
This study aims to determine the increase of liquidity ratio, solvency, profitabilityand activity on Javenir Shop souvenirs and souvenirs. Data collection method used in this research is descriptive qualitative research using financial report Javenir Souvenir and Souvenir Center in 2014-2016. The results showed that in the liquidity ratio of CR in the year 2014 decreased to 2015 and again rose in 2016, as well as with QR, the solvency ratio of DAR has has consistently improved over in 2014 to 2016 whereas in DER has onsistently improved over By 2014 to 2016, TATO's activity ratios have consistently risen from 2014 to 2016, and the profitability ratios of NPM in 2014 increased in 2015 but declined in 2016 and ROA has consistently increased in 2014 to 2016.